The role of banks: Evidence from Germany and the US - Elisabet Brichs Serra; Claudia M. Buch; Thomas Nienaber (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
In the discussion about the structure and evolution of financial systems, the US separated and the German universal banking system are commonly considered as antipodes. This paper shows that the differences in the role of banks in these two economies are less pronounced than the conventional wisdom suggests. Furthermore, prevailing differences can be explained by a number of factors other than banking regulations. Hence, the distinction which is commonly drawn between universal and separated banking systems can be misleading and tends to underrate the ongoing convergence between the systems.
Keywords: G1; G2; G32; 330; Bankensystem; Finanzintermediär; Bankenpolitik; Institutionalismus; Deutschland; USA